Inquiry Based Learning on Teaching Speaking to Students Second Semester of English Language Education - Kurniawati, Dyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Ghe aims of this study to determine the implementation of inquiry based learning strategy in learning speaking on the materials speaking for specific purpose and analyze students' responses to the implementation of inquiry based learning strategy. This research is a type of field research, and the approach used is qualitative approach. The researcher obtained data by using the technique of observation checklist, questionnaires, and documentation. Then the researchers’ classified the data according to the identified problem. In addition, the data were compiled and then analyzed by using descriptive analysis method. The results of this study indicate that the implementation of inquiry based learning strategy in learning speaking can be implemented well in accordance with the existing concept. Implementation was done through the activities of students looking for or digging information about learning materials, teacher provide stimulus and motivation to students followed by giving questions to students by teachers. The next step teacher provide opportunities to students in turns to provide responses or practice a conversation have discussed by students in pairwork, and at the end of the lesson teacher provide learning conclusions and reinforcement of learning materials that have been implemented. Students’ response to the implementation of strategy inquiry based learning positive about the strategy applied in learning. It make student learning outcomes become increased.